Qualitative research in Education in Brazil: consolidation and development (Research, Society and Development, 2019)
This paper aims to discuss how qualitative research has developed and consolidated in the context of Brazilian education, taking into account the chronology of the most diverse historical cycles that gave support to the theoretical-methodological foundations of the research in Education in Brazil. From this empirical bibliographical work that was based on the different sources, which approached reflections and problematizations of the methodological questions, it was demonstrated that the Brazilian educational thought passed through different cycles in the history of the Brazilian education, having configurations that are historically proven in the productions of the scientific work. For this discussion, consecrated authors were used to discuss qualitative research in the Brazilian educational context, such as Marcos Suel Zanette, who rescues the historical cycles of qualitative research in Brazil, as well as Bernadette Gatti which brings in its discussions the relevance of qualitative research methods in education. The study themes in the qualitative researches were extended over time, as well as the opening and implantation of masters and doctorates, which suffered foreign influences mainly in terms of methodology. In addition, there was a great incentive that provided this training abroad, resulting in the performance of teachers with specialization in academic work, teaching and research.